What stressors and energizers do PhD students in medicine identify for their work: A qualitative inquiry. (4th May 2022) - Kusurkar, Rashmi A.; Isik, Ulviye; van der Burgt, Stéphanie M. E.; Wouters, Anouk; Mak-van der Vossen, Marianne
Abstract: Introduction: Rising mental health issues is a global problem among PhD students. This study aimed to identify stressors and energizers in PhD work. Methods: PhD students at a university medical center were asked to describe the top three stressors and energizers in their PhD work through a survey. The narrative answers were subjected to content analysis. Results: Three hundred and eighty-six PhD students participated. We identified five overarching themes: Research is challenging, Resources can be limited, Recognizing the value of work, Experience of autonomy, and Relationships are key to success. We found positive (energizers) as well as negative (stressors) comments for each theme. Discussion: Supportive supervision with open communication has been identified in the literature as the most important contributor to PhD student well-being, while work-life imbalance has been identified as the most important reason for psychological distress. With our study, we add energizers and stressors that fit into a theoretical framework (Self-determination theory). This helps to understand the problem better and provide specific recommendations. Conclusions: Optimal challenges, resources and supervision, autonomy and good relationships at work are perceived as energizers. Challenges in research beyond capability, limitations in resources, not being valued, autonomy restriction and poor relationships at work are perceived as stressors in PhD work.